PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS VIDEO SPARKOL DENGAN MENGGUNAKAN MEDIA INTERNET DALAM PEMBELAJARAN MATEMATIKA SMP NEGERI 1 DAN 2 KECAMATAN TANAH JAWA - Imeldawaty Gultom; Marto Sihombing; A M H Pardede (STMIK KAPUTAMA, 2021)
The existence of the internet and all existing facilities can provide new knowledge or browse teaching materials for teachers so that the internet is an easier learning medium and can enrich teachers' insights. This study aims to determine the use of sparkol video as a learning resource for mathematics teachers of SMP Negeri Tanah Jawa District. Sparkol video-based internet learning media is made with the Videoscribe application, as a learning medium that can be used in schools and outside of school. The research aims to develop learning media that can be accessed freely on the Internet. Sparkol video-based internet learning model used is videoscribe which is open and mass. The learning curriculum also provides a set of learning tools covering, various questions, quizzes, and forms of assignments. The research implementation steps follow the general pattern of scientific research with an object-oriented approach with the stages of identification (identification), analysis (analysis), design (design), coding (programming) and testing (testing). This study produced an outcome that was targeted at the results of this study in the form of articles to be published in an Accredited National Journal. This article also aims to disseminate the results of research and science that can be used to broaden the knowledge and development of science in the future, especially in finding association rules between indicators of achieving competency standards tested in mathematics.